Cardiac arrhythmia services in Africa from 2011 to 2018: the second report from the Pan African Society of Cardiology working group on cardiac arrhythmias and pacing. Issue 3 (28th January 2020) - Bonny, Aimé; Ngantcha, Marcus; Yuyun, Matthew F; Karaye, Kamilu M; Scholtz, Wihan; Suliman, Ahmed; Nel, George; Aoudia, Yazid; Kane, Adama; Moustaghfi, Abdelhamid; Okello, Emmy; Houenassi, Martin; et al.
Abstract: Aims: Cardiac arrhythmia services are a neglected field of cardiology in Africa. To provide comprehensive contemporary information on the access and use of cardiac arrhythmia services in Africa. Methods and results: Data on human resources, drug availability, cardiac implantable electronic devices (CIED), and ablation procedures were sought from member countries of Pan African Society of Cardiology. Data were received from 23 out of 31 countries. In most countries, healthcare services are primarily supported by household incomes. Vitamin K antagonists (VKAs), digoxin, and amiodarone were available in all countries, while the availability of other drugs varied widely. Non-VKA oral anticoagulants (NOACs) were unequally present in the African markets, while International Normalized Ratio monitoring was challenging. Four countries (18%) did not provide pacemaker implantations while, where available, the implantation and operator rates were 2.79 and 0.772 per million population, respectively. The countries with the highest pacemaker implantation rate/million population in descending order were Tunisia, Mauritius, South Africa, Algeria, and Morocco. Implantable cardioverter-defibrillator and cardiac resynchronization therapy (CRT) were performed in 15 (65%) and 12 (52%) countries, respectively. Reconditioned CIED were used in 5 (22%) countries. Electrophysiology was performed in 8 (35%) countries, but complex ablations only in countries from the Maghreb and South Africa. Marked variation in costs of CIED that severely mismatched the gross domestic product per capita was observed in Africa. From the first report, three countries have started performing simple ablations. Conclusion: The access to arrhythmia treatments varied widely in Africa where hundreds of millions of people remain at risk of dying from heart block. Increased economic and human resources as well as infrastructures are the critical targets for improving arrhythmia services in Africa.